Kajian Manajemen Pemeliharaan Jalan Berdasarkan Korelasi Nilai Kerusakan terhadap Nilai Roughness Jalan Berbasis Roadlab-Pro - Yulandi, Wiki; Putri, Elsa Eka; Purnawan, Purnawan (Universitas Batanghari Jambi, 2025)
Road infrastructure is a critical component of land transportation systems, supporting both human mobility and the distribution of GOODs. To ensure user safety and comfort, roads must be maintained in optimal condition through appropriate and sustainable maintenance strategies. This study aims to formulate a road maintenance management strategy based on an analysis of the relationship between the International Roughness Index (IRI), as obtained through the Roadlab Pro application, and the extent of road damage as assessed by the Pavement Condition Index (PCI) method and the Bina Marga standard. A quantitative-descriptive method was employed, focusing on a 3-kilometer section of the Pondok–Pulau Sangkar Road in Kerinci Regency. Data were collected through a seven-day field survey, which included IRI measurements and visual damage assessments. The analysis revealed a very strong negative correlation between IRI and PCI values, indicating that higher IRI scores correspond to worse road conditions. Based on these findings, three maintenance budget planning scenarios were proposed: (1) maintenance based on actual damage, (2) routine annual maintenance, and (3) road upgrading in the first year, routine maintenance in the second year, followed by periodic maintenance from the third to the fifth year. The cost estimates encompass periodic, preventive, corrective, and routine maintenance, providing a comprehensive basis for medium-term planning. In conclusion, this study demonstrates that IRI data obtained from Roadlab Pro can serve as a reliable and efficient reference for evaluating road conditions and developing effective maintenance strategies based on the PCI approach.